CONTEXTUAL FACTOR IN GUESSING WORDS' MEANING IN READING BY EFL LEARNERS - Magdalena Marpaung; Humiras Betty Marlina Sihombing (LPPM Universitas Darma Agung, 2019)
Guessing words’ meaning by context clues can be resulted various depends on the contextual factors affected the process; richness factor, local-global factor, partial factor, and clear-ambiguous factor. The question lies in this article is ‘what is contextual factor mostly affected guessing words’ meaning in reading by the EFL learners?’ After taking data from 23 subjects by the instrument of observational test, the data analysis resulted as follow (1) context clues is positively contributed to the score of guessing words’ meaning in reading by the percentage 62,17% of correct answer, (2) both of richness factor and local-global factor are consistent to the theory, the rich-local factor is the most factor affect the guessing words’ meaning by the percentage of 69,56%, (3) after comparing the results of richness factor and local-global factor, it is resulted that richness factor is the factor which is mostly affect the guessing words’ meaning in reading by the percentage of 64,28% followed by the local-global factor by the percentage of 62,42%.